Re-Symbolization of the Self Human Development and Tarot Hermeneutic - Semetsky, Inna.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2011)
Bringing together popular and academic cultures, Inna Semetsky presents Tarot as a system of transformative hermeneutics for adult self-education and cultural pedagogy. Her research is a decisive and intelligent step ahead from the reductive stereotype of Tarot as fortune-telling. The fifteen life stories at the heart of the book exemplify the author$1 (Bs commitment to alternative modes of education and counseling that transcend individual, cultural or language barriers. Assembling a rich array of sources, from Hermeticism to Jungian depth psychology, the philosophies of Noddings, Buber, and Deleuze, and the science of self-organization, this book opens a new path to personal and social revitalization. It should be widely read across disciplinary divides by scholars, students, and professionals alike.s
Keywords: Education; Education -- Philosophy; Education; Educational Philosophy